Changes in hydrodynamics and nutrient load of the coastal bay induced by Typhoon Talim (2023) - Chen, Chunqing; Lao, Qibin; Zhou, Xin; Zhu, Qingmei; Chen, Fajin (Frontiers in Marine Science, 2024)
Typhoons can greatly alter the hydrodynamic and nutrient supply in coastal oceans. However, due to the complex conditions of typhoons, such as their intensity, even slight changes may cause substantial changes in hydrodynamics and nutrient supply, which needs to be better understood. In this study, we conducted two cruises before and after Typhoon Talim (2023) to quantitatively investigate changes in hydrodynamics and nutrient supply in Zhanjiang Bay using dual water isotopes. Before the typhoon, strong stratification occurred in the bay. However, the strong external force of the typhoon destroyed the stratification and substantially changed the water mixing in the bay after the typhoon. In the upper bay, massive freshwater input remarkably decreased the salinity during the post-typhoon period (freshwater increased by 18%). In contrast, the salinity variation in the lower bay was minimal, mainly due to massive seawater intrusion from the outer bay induced by the typhoon; the seawater mixed with freshwater columns from the upper bay, forming a strong ocean front. The intensity of ocean fronts induced by typhoons directly depended on the typhoon intensity landing in Zhanjiang Bay, as stronger typhoons will cause more intrusion of high-salinity seawater from the outer bay. Due to the formation of the ocean front, freshwater and terrestrial nutrients from the upper bay are prevented from being transported downwards, resulting in a large amount of accumulated pollutants within the bay. By contrast, due to the impact of high-salinity seawater intrusion, the contribution of seawater from the outer bay has increased, thereby diluting the nutrients in the lower bay. This study provides a new insight into the responses of coastal marine eco-environment systems to typhoons.